اصحابِ اخدود كے بارے میں جمہور مفسرین اور محدثین كے اقوال كا جائزہ: Analysis of mainstream Interpreters and Muhaddithin’s exegesis about People of the Ditch (Khairulummah, 2023)
Allah has mentioned many nations in his Holy book Quran for the purpose of guidance because in their stories there are messages for the believers just as Allah said in Quran, “Indeed in their stories, there is a lesson for men of understanding. It (the Quran) is not a forged statement but a confirmation of the Allah's existing Books [the Taurat (Torah), the Injeel (Gospel) and other Scriptures of Allah] and a detailed explanation of everything and a guide and a Mercy for the people who believe” [12:111]Among nations mentioned in the Quran are people of the ditch who are cursed in Sura AL-BURUJ (the big stars), but the Interpreters of Quran and Hadith have differed in determining the people of ditch who they really were and what was the main reason that Allah has cursed them.
Keywords: People of the Ditch; Allah